Application of aquatic mosses to decontaminate industrial effluents - Martins, Ramiro (2012)
As biosorption is a low cost and effective method for treating metal-bearing wastewaters, understanding the process kinetics is relevant for design purposes. In the present study, the performance of the aquatic moss Fontinalis antipyretica for removing cadmium and lead from simulated wastewaters has been evaluated. Five kinetic models (first-order, pseudo-first-order, Elovich, Ritchie second-order and pseudo- second-order) were fitted to the experimental data and compared. Previously, the effect of parameters such as the initial solution pH, contact time, and initial metal ion concentration on biosorption was investigated using a sorbent dose of 2 g l-1. The initial pH of the solution was found to have an optimum value in the range of 4.0-6.0. The equilibrium sorption capacity of cadmium and lead by Fontinalis antipyretica increased with the initial metal concentration. For an initial metal concentration of 10 mg l-1, the uptake capacity of the moss, at equilibrium, is the same for both metals (4.8 mg g-1). Nevertheless, when the initial concentration increases up to 100 mg l-1, the uptake of Pb(II) is higher than 78%. The pseudo-second order biosorption kinetics provided the better correlation with the experimental data .